2020
DOI: 10.1016/j.cortex.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating words during spoken discourse comprehension: A large-scale, pre-registered replication study using brain potentials

Abstract: Numerous studies report brain potential evidence for the anticipation of specific words during language comprehension. In the most convincing demonstrations, highly predictable nouns exert an influence on processing even before they appear to a reader or listener, as indicated by the brain's neural response to a prenominal adjective or article when it mismatches the expectations about the upcoming noun. However, recent studies suggest that some well-known demonstrations of prediction may be hard to replicate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 93 publications
(197 reference statements)
1
4
0
Order By: Relevance
“…Only for the two correlations between the electric field induced in BA44 and the First P600 BA44 and Second ESN BA44 effects "anecdotal" evidence was provided, with BF 01 being 2.159 and 2.468, respectively. Importantly, the strength of evidence reported in our study converges on the one which is present in the literature in TMS (Kuhnke et al, 2020) and EEG (Nieuwland et al, 2020) studies employing Bayesian statistics. The BFs factors from the present study provide the first estimation of the evidence in favour of the null hypothesis on a continuous scale (Faulkenberry et al, 2020), on which future studies can be based.…”
Section: Limitationssupporting
confidence: 86%
See 1 more Smart Citation
“…Only for the two correlations between the electric field induced in BA44 and the First P600 BA44 and Second ESN BA44 effects "anecdotal" evidence was provided, with BF 01 being 2.159 and 2.468, respectively. Importantly, the strength of evidence reported in our study converges on the one which is present in the literature in TMS (Kuhnke et al, 2020) and EEG (Nieuwland et al, 2020) studies employing Bayesian statistics. The BFs factors from the present study provide the first estimation of the evidence in favour of the null hypothesis on a continuous scale (Faulkenberry et al, 2020), on which future studies can be based.…”
Section: Limitationssupporting
confidence: 86%
“…Third, recent data suggest that a careful examination of apparent pre-activation effects is necessary (Nieuwland, 2019). While initial data supported the hypothesis that probabilistic information can be used to anticipate properties of upcoming words up to the phonological level (Delong et al, 2005;Van Berkum et al, 2005), recent large-scale replication studies question this notion (Nieuwland et al, 2018(Nieuwland et al, , 2020. Similarly, the modulation of the ELAN by structural predictions originally reported by Lau et al (2006) was not replicated by a follow-up study (Kaan et al, 2016; see also Nieuwland, 2019 for a discussion of Lau et al, 2006 findings).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that humans are able to predict upcoming input on the basis of perceptual, social, and linguistic cues (e.g., Kamide et al, 2003 ; Winkler et al, 2009 ; Ridderinkhof, 2017 ; see also Litwin and Miłkowski, 2020 ). As far as linguistic prediction is concerned, studies have shown that material can be pre-activated at different levels of linguistic representation, from phonologically- and lexically-driven pre-activation to pre-activation derived from syntactic and semantic cues (e.g., Mani and Huettig, 2012 ; Boudewyn et al, 2015 ; Urbach et al, 2015 ; Kuperberg and Jaeger, 2016 ), although some of these findings—particularly with respect to phonological prediction—have failed to replicate in more recent studies (e.g., Nieuwland et al, 2020 ; see also Kuperberg and Jaeger, 2016 for a detailed discussion of the different sorts of prediction potentially involved in predictive language processing). As for pragmatics, many studies have provided evidence that high-level semantic and pragmatic prediction occurs while people process language, from the processing of negation (e.g., Nieuwland, 2016 ; Haase et al, 2019 ; see also Scappini et al, 2015 ; Darley et al, 2020 ) to the processing of sentences containing potentially pragmatic cues such as the scalar quantifier some (e.g., Nieuwland et al, 2010 ; Augurzky et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other ERP studies investigating morphosyntactic constraints (Foucart, et al, 2014;Martin, et al, 2018;Otten & Van Berkum, 2009;Wicha, Moreno, & Kutas, 2004), phonotactic constraints (Martin, et al, 2013), or both (Ito, et al, 2020) report evidence for pre-activation of target nouns on preceding articles. Although some studies have not successfully replicated these effects (Ito, Martin, & Nieuwland, 2017;Nieuwland, Arkhipova, & Rodríguez-Gómez, 2020;Nieuwland, et al, 2018), taken together this research has underpinned theories of prediction in language comprehension by providing unambiguous evidence for predictive processes.…”
Section: Introductionmentioning
confidence: 94%